Perkawinan Usia Dini: Menggali Aspek Hukum dan Sosial Pengesahan untuk Anak di Bawah Umur - Fayzah Nazmah; Aldo Yanuarto; Alviiianur Alviiianur; Muhammad Rifky; A. Dzulqarnain (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
The legalization of marriage or isbat nikah is a legal process regulated in Undang-Undang Nomor 1 Tahun 1974in Indonesia, aiming to provide legal certainty and protection for married couples. The study focused on cases of marriage legalization in Martapura, South Kalimantan, from 2021 to 2022, which identified challenges in implementing regulations, especially related to unofficially registered marriages and the practice of underage marriage. The study results show that although there are clear legal provisions, their implementation is often influenced by the social and cultural norms of the community. The cases rejected and granted by judges reflect the complexity of handling serial marriages, where there is a conflict between state law and religious validity. A holistic approach is needed to raise awareness of the importance of marriage registration and protecting children's rights so that all marriages can be legally recognized.